PENERAPAN KOMUNIKASI PARTISIPATORY DALAM PENYELENGGARAAN IDXCARBON PADA BEI - Hardjanti, Rani; S. Bekti Istiyanto; Drina Intyaswati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The implementation of carbon trading through the IDXCarbon platform, managed by the Indonesia Stock Exchange (IDX), marks a strategic step in supporting Indonesia’s commitment to reducing carbon emissions. However, the success of this initiative is highly influenced by the communication strategies employed, particularly participatory communication that engages multiple stakeholders. This study aims to analyze how participatory communication is applied by IDX in the development of IDXCarbon and in fostering public and stakeholder engagement. A descriptive qualitative method with a case study approach was used. Data were collected through interviews, observations, and documentation. The findings indicate that IDX has applied participatory communication principles through eight key elements: dialogue, active participation, empowerment, cultural contextualization, access and equity, collectivity, transparency, and feedback. These elements are reflected in various initiatives such as public education programs, newsletters, discussion forums, and the "Pojok Bursa" (IDX Corners) established in universities. Nevertheless, challenges remain in reaching new participants and improving carbon literacy. Therefore, strengthening participatory communication is essential to ensure the sustainability of IDXCarbon and to promote inclusive and widespread engagement. In conclusion, effective participatory communication can enhance public trust, strengthen cross-sector collaboration, and support Indonesia’s efforts to achieve net zero emissions by 2060.